THE CORRELATION BETWEEN GRAMMAR MASTERY AND SPEAKING SKILL OF THE ELEVEN GRADE STUDENTS OF SMAN 1 KOTO KAMPAR HULU - Ulfa, Nadiah; Hardi, Vitri Anggraini; Ayu, Citra (Universitas PGRI Sumatera Barat, 2022)
This study sought to determine the relationship between students' speaking abilities and their command of grammar. The correlation approach was applied in this study. Students in SMAN 1 Koto Kampar Hulu's eleventh grade made up the study's population. There were 31 pupils in the sample, and random sampling was used. Grammar tests and interview tests were two different types of tools. According to the research, the grammar proficiency of the eleventh graders at SMAN 1 Koto Kampar Hulu was rated as inadequate. The students' speaking ability was rated as fair and represented by the mean score (69, 52). The average score revealed it (70,32). The rate of correlation between students' speaking prowess and their command of grammar was at a